2018
DOI: 10.1088/2040-8986/aac1d5
|View full text |Cite
|
Sign up to set email alerts
|

High-power waveguide resonator second harmonic device with external conversion efficiency up to 75%

Abstract: We report on a highly efficient waveguide resonator device for the production of 775 nm light using a titanium indiffused LiNbO3 waveguide resonator. When scanning the resonance the device produces up to 110 mW of second harmonic power with 140 mW incident on the device -an external conversion efficiency of 75%. The cavity length is also locked, using a Pound-Drever-Hall type locking scheme, involving feedback to either the cavity temperature or the laser frequency. With laser frequency feedback a stable outpu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 40 publications
(76 reference statements)
0
13
1
Order By: Relevance
“…From these results, an enhancement factor of the coupling constant is estimated to be 13. While the value is slightly smaller than a theoretically predicted value [25,26] F/π ∼ 19 with finesse F = 59 [23], our result surely showed that the coupling strength becomes an order of magnitude larger. This statement holds in comparison to other QFC experiments using PPLN waveguides without cavities in various situations [14][15][16][17][18][19] in which the coupling constant from 0.003 to 0.012 W −1 mm −2 were observed.…”
Section: (E)contrasting
confidence: 73%
“…From these results, an enhancement factor of the coupling constant is estimated to be 13. While the value is slightly smaller than a theoretically predicted value [25,26] F/π ∼ 19 with finesse F = 59 [23], our result surely showed that the coupling strength becomes an order of magnitude larger. This statement holds in comparison to other QFC experiments using PPLN waveguides without cavities in various situations [14][15][16][17][18][19] in which the coupling constant from 0.003 to 0.012 W −1 mm −2 were observed.…”
Section: (E)contrasting
confidence: 73%
“…for Ti:LN waveguides We now apply the previous theory to titanium in-diffused lithium niobate (Ti:LN) waveguides in order to study the technological limits of this platform. Ti:LN waveguides have been widely used for classical and quantum applications [5,6,[27][28][29][30][31][32]. They exhibit extremely low propagation losses (<0.1 dB cm −1 ), can guide both TE and TM polarization modes, possess high nonlinearity, allow on-chip manipulation of the light field via integrated beamsplitters and acousto-and electrooptical modulators and can be easily interfaced to fibre network via pigtailing [14].…”
Section: Numerical Analysis Ofmentioning
confidence: 99%
“…The reflectance for 1540 nm is about 30 % which is a little bit larger but forms a very lossy cavity. This should give no cavity enhancement effect for the frequency conversion considering its finesse smaller than π [24,25].…”
mentioning
confidence: 99%

Optical frequency tweezers

Ikuta,
Yokota,
Kobayashi
et al. 2021
Preprint